PENGARUH KINERJA KARBON, KARAKTERISTIK PERUSAHAAN DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN EMISI KARBON - Selviana Selviana; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
This research aims to examine and obtain empirical evidence about factors that influence carbon emission disclosure on firms operate in Indonesia. Factors that examined in this research are carbon performance, firm size, profitability, leverage, capital expenditure, level of information asymmetry and environmental performance. The population in this study are companies listed on Indonesia Stock Exchange. This study used purposive sampling method, namely sampling based on certain criteria: published their annual report and sustainability report for the year 2013 – 2017 and make an explicit carbon emission disclosure. Nine companies become the final sample in this research. The result implies that firm size and capital expenditure have significant positive correlation with carbon emission disclosure. Meanwhile, profitability and leverage have significant negative correlation with carbon emission disclosure. This result also implies that carbon performance, level of information asymmetry and environmental performance do not provide significant effect with carbon emission disclosure.